Rosacea – atypical forms - Sielska, Halina; Seneczko, Michał (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2003)
Rosacea is a common, chronic dermatosis characterized by facial flushing, erythema, teleangiectasia, inflammatory episodes with papules and pustules and, in severe cases, rhinophyma. It appears more often in women, but is more severe in men. Atypical forms of rosacea which we want to present include ocular rosacea, steroid rosacea, fulminating rosacea, persistent erythema, lupoid rosacea, disseminated rosacea, extrafacial rosacea, rosacea in an HIV-positive patient, childhood rosacea and perioral dermatitis which is recognized rather as similar to rosacea.